Human Rights Act 1998 and mental health legislation: implications for the management of mentally ill patients - Leung, W (BMJ Group, 2002)
This article first examines the extent to which the Mental Health Act 1983 is consistent with the Human Rights Act. It argues that while the recent white papers exploit the gaps in the judgments given by the European courts, its compatibility with human rights is very doubtful. The practical implications of the Human Rights Act for doctors are discussed.